Earnings Management in Retail Industry: Indonesian Listed Firms - Tristany, Chelsie (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2020)
Agency problem encourages the use of contracts to mitigate the conflict of interest between investors and managers. The use of reward contract incite discretionary actions from the managers